Activities for teaching psychology and law a guide for instructors - Zelechoski, Amanda D.; Wolbransky, Melinda; Riggs Romaine, Christina L. (American Psychological Association, 2018)
"This book presents a wide variety of experiential learning activities to help instructors enliven their courses and teach critical concepts in psychology and law. The activities incorporate individual and group work, videos, reading materials, classroom discussions, homework assignments, and lots of role play. A companion website provides free modifiable handouts and videos to support the activities. With clear instructions and guidance, this book provides everything needed to implement the activities"--Supplied by publisher.